2012
DOI: 10.1103/physrevlett.108.157604
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Clamping Effects on Irreversible Domain Wall Dynamics in Lead Zirconate Titanate Thin Films

Abstract: The role of long-range strain interactions on domain wall dynamics is explored through macroscopic and local measurements of nonlinear behavior in mechanically clamped and released polycrystalline lead zirconate-titanate (PZT) films. Released films show a dramatic change in the global dielectric nonlinearity and its frequency dependence as a function of mechanical clamping. Furthermore, we observe a transition from strong clustering of the nonlinear response for the clamped case to almost uniform nonlinearity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
83
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 118 publications
(89 citation statements)
references
References 42 publications
6
83
0
Order By: Relevance
“…Use of a more compliant substrate (than Si, for example) may reduce substrate clamping and improve the effective piezoelectric properties [11,12]. Griggio et al recently directly demonstrated the negative effect of substrate clamping on domain mobility [13]. Copper foil is also a candidate for transducers with non-planar geometries.…”
Section: Introductionmentioning
confidence: 98%
“…Use of a more compliant substrate (than Si, for example) may reduce substrate clamping and improve the effective piezoelectric properties [11,12]. Griggio et al recently directly demonstrated the negative effect of substrate clamping on domain mobility [13]. Copper foil is also a candidate for transducers with non-planar geometries.…”
Section: Introductionmentioning
confidence: 98%
“…It has been suggested that the different mechanical state of PZT films modifies the density and motion of non-180 domain walls and the polarization switching behavior to accommodate the strain, leading to a significant change in their piezoelectric and dielectric properties. [6][7][8] The contribution of the extrinsic parameters to an increase in the dielectric permittivity and tunability under biaxial tensile stress has been observed in other typical ferroelectric materials, (Ba,Sr)TiO 3 (BST). 9,10 Previous reports have also shown that mechanical stresses in ferroelectric films can affect the fatigue and imprint behavior, which have plagued the application of ferroelectric materials by changing the stability and the dynamics of domains under an external electric field.…”
mentioning
confidence: 95%
“…[15,16] In fact, recent studies have illustrated the unexpectedly large role of clamping on the electromechanical response of PZT thin films, suggesting the presence of nontrivial, large length-scales for strain interactions present in such samples. [17] Similarly, evidence has also been provided of avalanche-like behavior of multiple domain walls due to cooperative interactions across these large length scales in disordered ferroelectric thin films. [18] These considerations suggest that the role of local strains on ferroelectric and ferroelastic properties is central to both the piezoelectric and ferroelectric phenomena themselves.…”
Section: Introductionmentioning
confidence: 99%